PENGARUH E-SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION MELALUI PERCEIVED VALUE PELANGGAN APLIKASI GRAB FOOD DI KOTA MAKASSAR - Bahtiar Bahtiar; Buyung Romadhoni; Muchriady Muchran (COMPETITIVENESS, 2021)
This study aims to determine the effect of E-service quality on customer satisfaction through the customer's perceived value of the Grab Food application in Makassar City. This research is experimental, the research design used is associative research. associative or relationship is research that aims to determine the relationship between two or more variables. The research data obtained that E-service quality has a significant positive effect on Perceived value with P = 0.000 0.05 with a coefficient value of 0.500, this coefficient indicates that the better the E-service quality perceived by consumers, the better the perceived value will also be, and Perceived value has a significant positive effect on customer satisfaction with P = 0.000 0.05 with a coefficient value of 0.233, this coefficient indicates that the better the perceived value, the better customer satisfaction, while E-service quality has a significant positive effect on customer satisfaction with P = 0.000 0.05 with a coefficient value of 0.547, this coefficient indicates that the better the E-service quality perceived by consumers, the more customer satisfaction will increase. And finally, E-service quality has a significant influence on customer satisfaction through Perceived value with a coefficient value of 0.274, this coefficient indicates that good service quality perceived by consumers will encourage consumers to increase perceived value for products and ultimately have an impact on better consumer satisfaction.Keywords: E-service quality, Customer satisfaction, and Perceived Value.